Sensory Processing in Rhesus Monkeys: Developmental Continuity, Prenatal Treatment, and Genetic Influences. Issue 1 (24th June 2016) - Schneider, Mary L.; Moore, Colleen F.; Adkins, Miriam; Barr, Christina S.; Larson, Julie A.; Resch, Leslie M.; Roberts, Andrew
Abstract : Neonatal sensory processing (tactile and vestibular function) was tested in 78 rhesus macaques from two experiments. At ages 4–5 years, striatal dopamine D2 receptor binding was examined using positron emission tomography. At ages 5–7 years, adult sensory processing was assessed. Findings were: (a) prenatal stress exposure yielded less optimal neonatal sensory processing; (b) animals carrying the short rh5‐HTTLPR allele had less optimal neonatal sensory scores than monkeys homozygous for the long allele; (c) neonatal sensory processing was significantly related to striatal D2 receptor binding for carriers of the short allele, but not for animals homozygous for the long allele; and (d) there was moderate developmental continuity in sensory processing from the neonatal period to adulthood.